ANALISIS PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN INFLASI TERHADAP NILAI PERUSAHAAN SEKTOR INFRASTRUKTUR DI BEI - Ahmad Naufali Azmi (2023)
The purpose of this study was to determine the effect of the value of infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) with factors originating from external and internal companies. The company's internal factors use profitability proxied by Return on Equity (ROE), liquidity proxied by Current Ratio (CR), and leverage proxied by Debt to Equity Ratio (DER), while the external factor used is inflation. The object of this research is infrastructure companies listed on the Indonesia Stock Exchange (IDX) in the period 2017 - 2022. The sample used is an infrastructure company listed on the Indonesia Stock Exchange (IDX) that has and has published its financial statements during the study period totaling 47 companies. This study uses data for a period of 6 years resulting in 282 research data. The data processing method used in this research is the panel data regression model with the help of Eviews - 12 as a data processing tool. The results of this study are profitability (ROE), liquidity (CR), and leverage (DER) have a significant effect on stock prices in a positive or unidirectional direction. While inflation has no significant effect on stock prices in a positive or unidirectional direction